Improving Attitudes Toward Psychotherapy in Residents and Syrian Refugees in Germany: An Interview Vignette Intervention Study. (June 2023) - Schlechter, Pascal; Hellmann, Jens H.; Kamp, Svea; Echterhoff, Gerald; Wanninger, Katharina; Wagner, Ullrich; Knausenberger, Judith
Syrian refugees underutilize mental health services in Western receiving countries, which is partly attributable to negative attitudes toward seeking professional psychological help (APPH) and denial of the need for psychological help (DNPH). Interventions tailored to culture-specific characteristics of Syrian refugees are needed. We tested an intervention that disseminated information about the benefits of psychotherapy via ostensible interview vignettes to 205 German residents and 187 Syrian refugees residing in Germany. We used a 2 (group: residents vs. refugees) × 2 (source of information: ingroup vs. outgroup member) × 2 (therapy content: skill training vs. emotion regulation) × 2 (gender: women vs. men) between-participants design with the dependent variables APPH and DNPH. We measured adherence to masculine norms, support by religious faith, and distress disclosure as additional predictors. Refugees reported more negative APPH and higher DNPH than residents. Source of information and therapy content had no detectable effect. Men reported more negative APPH and higher DNPH than women. Adherence to masculine norms emerged as the strongest predictor of APPH. Masculine norms and support by religious faith partly explained differences between refugees and residents in APPH and DNPH. Exploratory post hoc analyses with nonintervention samples of 182 Syrian refugees and 202 residents from a similar study indicated that Syrian refugees who received an intervention (vs. no intervention) reported more positive APPH. No such difference was found for residents. Disseminating information about psychotherapy could positively impact APPH/DNPH in refugees but needs to be tailored to their sociocultural context. We outline recommendations for further research.